2018
DOI: 10.1002/jhet.3442
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 4‐Hydroxyquinolin‐2(1H)‐ones with Acenaphthoquinone: Synthesis of New 1,2‐Dihydroacenaphthylene‐spiro‐tetrakis(4‐hydroxyquinolin‐2(1H)‐ones)

Abstract: Reaction of four equivalents of 4‐hydroxyquinolin‐2(1H)‐ones with one equivalent of acenaphthoquinone in absolute ethanol, containing catalytic triethylamine, gave 3,3′,3″,3‴‐(1,2‐dihydroacenaphthylene)‐1,1,2,2‐tetrayl‐tetrakis(4‐hydroxyquinolin‐2(1H)‐ones) in a good to excellent yields. The structures of the products were elucidated by 1H NMR, 13C NMR, NMR, IR, mass spectra, and elemental analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…An example, 2,3-bis-(4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)succinic acid derivatives I , were obtained by one-pot reaction of one equivalent of aromatic amines with two equivalents of diethyl malonate in diphenyl ether and catalyzed with triethylamine [14]. On reacting four equivalents of 4-hydroxyquinolin-2(1 H )-ones with one equivalent of acenaphthoquinone in absolute ethanol, containing catalytic Et 3 N, the reaction gave acenaphthylene-1,1,2,2-tetrayl-tetrakis- (4-hydroxyquinolin-2(1 H )-ones) ( II , [15]. We also reported that quinoline-2,4-diones reacted with 2-(2-oxo-1,2-dihydroindol-3-ylidene)malononitrile in pyridine to give spiro(indoline-3,4′-pyrano- [3,2- c ]quinoline)-3′-carbonitriles ( III , [16].…”
Section: Instructionmentioning
confidence: 99%
See 2 more Smart Citations
“…An example, 2,3-bis-(4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)succinic acid derivatives I , were obtained by one-pot reaction of one equivalent of aromatic amines with two equivalents of diethyl malonate in diphenyl ether and catalyzed with triethylamine [14]. On reacting four equivalents of 4-hydroxyquinolin-2(1 H )-ones with one equivalent of acenaphthoquinone in absolute ethanol, containing catalytic Et 3 N, the reaction gave acenaphthylene-1,1,2,2-tetrayl-tetrakis- (4-hydroxyquinolin-2(1 H )-ones) ( II , [15]. We also reported that quinoline-2,4-diones reacted with 2-(2-oxo-1,2-dihydroindol-3-ylidene)malononitrile in pyridine to give spiro(indoline-3,4′-pyrano- [3,2- c ]quinoline)-3′-carbonitriles ( III , [16].…”
Section: Instructionmentioning
confidence: 99%
“…Structures of compounds that previously reported (Reproduced with permission from [14,15,16,17,18,19,20]).…”
Section: Figures and Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, 2,3-bis-(4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)succinic acid derivative I, was obtained by a one-pot reaction of one equivalent of aromatic amines with two equivalents of diethyl malonate in diphenyl ether and catalyzed with triethylamine [27] . A reaction of four equivalents of 4-hydroxyquinolin-2(1 H )-one with one equivalent of acenaphthoquinone gave acenaphthylene-1,1,2,2-tetrayl-tetrakis(4-hydroxyquinolin-2(1 H )-one) (II, [28] . We also reported that quinoline-2,4-dione reacted with 2-(2-oxo-1,2-dihydroindol-3-ylidene)malononitrile in pyridine to give spiro(indoline-3,4′-pyrano[3,2- c ]quinoline)-3′-carbonitrile (III, [29] , whereas 2-quinolone reacted with diethyl acetylenedicarboxylate to give pyrano[3,2- c ]quinoline-4-carboxylate (IV, [30] .…”
Section: Introductionmentioning
confidence: 99%
“…[19] In light of our general aim to screen compounds of biological and pharmaceutical importance, we designed, synthesized, and screened a large variety of biologically active compounds. [20][21][22][23][24][25][26][27] The total number of people with diabetes has been projected to increase from 171 million in 2000 to 366 million by 2030. Diabetes mellitus (DM) is managed by insulin and oral administration of hypoglycemic drugs such as sulfonylureas and biguanides.…”
mentioning
confidence: 99%